O‘ZBEK TILINI O‘RGANISH MAZMUNINI MINIMALLASHTIRISHNING ASOSIY TAMOYILLARI VA ZAMONAVIY METODLAR - Sultanova, A. (SCIENCE and SOCIETY, 2024)
This article will focus on modern techniques that help ensure consistency in Uzbek language lessons, as well as improve students' speech and language competence.
Keywords: textbook; integration; language education; literacy; interactive methods